Exploring the Role of 'English Club' Extracurricular Activities in Improving Students' Speaking Skills at SMKN 2 Kintamani - Anak Agung Putu Arsana; Putu Candrawati; Anisa Tri Cahyani (Journal on Studies in English Language Teaching (JOSELT), 2026)
Limited curricular time and high levels of language anxiety in formal classrooms often hinder the mastery of English for Specific Purposes (ESP)-based speaking skills for vocational high school students in tourism areas. This descriptive qualitative study aims to explore the multidimensional role of English Club extracurricular activities in improving students' speaking skills at SMK Negeri 2 Kintamani. Data were collected through passive participant observation, in-depth interviews with instructors, teachers, and students, as well as documentation study. The data were validated using triangulation techniques and subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate that the English Club, optimized during the Happy Friday program, successfully acts as a safe space that effectively reduces students' affective anxiety and triggers intrinsic motivation to communicate confidently. Theoretical discussion proves that this program successfully bridges the ESP needs of the Hospitality Accommodation Department through functional role-play methods, constructs sociolinguistic competence through the transformation of local culture into English 3S, and empowers students as subjects of sustainable tourism through local storytelling based on the potential of the Batur Geopark landscape and Tri Hita Karana cosmology.